PENGARUH KOMPETENSI AUDITOR TERHADAP PERENCANAAN AUDIT DENGAN DIMODERASI PEMAHAMAN TEKNOLOGI INFORMASI (STUDI EMPIRIS PADA AUDITOR DI KAP SEMARANG) - Adinda Rizky Larasati; Herry Laksito (Diponegoro Journal of Accounting, 2019)
This study aims to analyze the effect of auditor competency on audit planning by moderating understanding of information technology. This research was conducted on auditors working at the Semarang Public Accountant Office. There are two hypotheses in this study, including the influence of auditor competency on audit planning and understanding of information technology moderates the influence of auditor competence on audit planning.This study uses primary data obtained from the results of distributing questionnaires at the Semarang Public Accountant Office. The sampling method in this study is random sampling. This study uses a moderating regression analysis technique with a test of the absolute value difference.The results of the study indicate that auditor competence is able to influence audit planning significantly and positively. Not only that, the result of the study shows that understanding information technology cannot moderate the influence of auditor competence on audit planning.